Impact of tissue culture banana technology in Kenya: A difference-in-difference estimation approach - Enoch M. Kikulwe; Nassul .S. Kabunga; Matin Qaim (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2012)
Most micro-level studies on the impact of agricultural technologies build on cross-section data, which can lead to unreliable impact estimates. Here, we use panel data covering two time periods to estimate the impact of tissue culture (TC) banana technology in the Kenyan small farm sector. TC banana is an interesting case, because previous impact studies showed mixed results. We combine propensity score matching with a difference-in-difference estimator to control for selection bias and account for temporal impact variability. TC adoption has positive impacts on banana productivity and profits. The technology increases yields by 40-50% and gross margins by around 100%. These large effects represent the impact of TC technology in combination with improved management practices and higher input use, which is recommended. Looking at the isolated TC effect may underestimate impact because of synergistic relationships. The results suggest that extension efforts to deliver the technological package to smallholder farmers should be scaled up.
Keywords: 330; Agricultural technology; Difference-in-difference; Selection bias; Temporal impact variability; Impact; Kenya